Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4172/2471-9846.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Awareness in Nursing is a Progressive Growth

Abstract: During the past four decades, researchers have developed strategies used in nursing programs to promote cultural awareness. Minimal research has focused on the graduating associate degree-nursing students to determine if a relationship existed between the use of an integrated cultural curriculum and the nursing student's level of cultural awareness. The associate degree-nursing program accreditation, statistical and benchmark reports mandated the integration of diversity content, local, national and worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
2
0
0
1
Order By: Relevance
“…The highest rated subscale was NcC, which describes a teacher’s work during lectures on cultural competencies (e.g., “I feel that this nursing school’s instructors respect differences in individuals from diverse cultural backgrounds,” or “My instructors at this nursing school seem comfortable discussing cultural issues in the classroom.”). Thus, our findings correspond somewhat with other similar research using the CAS questionnaire (Safipour et al, 2016; Thornton, 2017). Since cultural competence is an essential skill for nurses, it is an important skill for nurse educators as well.…”
Section: Discussionsupporting
confidence: 93%
“…The highest rated subscale was NcC, which describes a teacher’s work during lectures on cultural competencies (e.g., “I feel that this nursing school’s instructors respect differences in individuals from diverse cultural backgrounds,” or “My instructors at this nursing school seem comfortable discussing cultural issues in the classroom.”). Thus, our findings correspond somewhat with other similar research using the CAS questionnaire (Safipour et al, 2016; Thornton, 2017). Since cultural competence is an essential skill for nurses, it is an important skill for nurse educators as well.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that students exhibit above average intercultural sensitivity levels, which is in line with other studies conducted in Türkiye (Akca & Ayaz-Alkaya, 2023;Alıcı, 2021;Baksi et al, 2019;Bilgiç & Şahin, 2019;Hergül et al, 2022;Kılıç & Sevinç, 2018;Yiğit et al, 2021;Yalçın & Öztürk, 2022;Yurttaş & Aras, 2020). However, it should be noted that studies in other countries have reported higher levels of intercultural sensitivity and cultural awareness among nursing students when compared to Türkiye (Ličen, Karnjuš, & Prosen, 2021;Muslu & Tuzcu, 2022;Thornton, 2017). This difference is believed to be due to the recent inclusion of cultural nursing approaches in nursing education curricula in Turkey and the absence of a standardized curriculum for cultural competence education.…”
Section: Discussionsupporting
confidence: 86%
“…Muslu ve Tuzcu'nun çalışmasında hemşirelik öğrencilerinin kültürel farkındalık puanı 172.49±30.25 olarak; Licen ve ark. tarafından Slovenya'da hemşirelik öğrencileri ile yapılan çalışmada 194.0±19.63 olarak; Thornton tarafından gerçekleştirilen çalışmada ise mezun olan hemşirelik öğrencilerinin kültürel farkındalık ölçeğinden en düşük 171.0, en yüksek 237.0 puan aldıkları bildirilmektedir (Ličen, Karnjuš, & Prosen, 2021;Muslu ve Tuzcu,2022;Thornton, 2017). Safipour ve ark.…”
Section: Discussionunclassified